Asymmetric synthesis of aminocyclooctenecarbonitriles: Cyclooctene ?-lactam and hydroxyaminocyclooctene carboxylic precursors - Aydin, Busra Ozturk; Yurtoglu, Emine; Arcelik, Nejat; Sahin, Ertan; Secen, Hasan; Altundas, Ramazan (Pergamon-Elsevier Science Ltd, 2019)
Enantiopure beta-aminocyclooctenenitriles, as precursors of beta-amino acids and beta-lactams, were synthesized from a readily available chloroalkene nitrite and (S)-methylbenzylamine via a straightforward substitution reaction and purified by crystallization. Acidic hydrolysis of the nitrite groups to their corresponding amides followed by DCC assisted carbonyl group activation gave novel alpha,beta-unsaturated lactams. The treatment of 3-bromo-8-chlorocyclooctenecarbonitrile with (S)-methylbenzylamine furnished a diastereomeric mixture of bromoaminocyclooctenecarbonitriles via an S(N)2' pathway rather than bromide substitution via an S(N)2 pathway. The diastereomeric mixture of bromoaminocyclooctanecarbonitriles provided two novel aziridines upon heating. TFA catalyzed aziridine ring opening gave gamma-hydroxyl-beta-aminocyclooctenecarbonitriles and gamma-amino-beta-hydroxycyclooctenecarbonitriles. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Aminocyclooctenecarbonitrile; Hydroxyaminocycloctene nitrite; Cycloctenelactams